• 28-01-2007 16:14
  • Просмотры: 55
Ответы ( 1 )
МИТЯ ЛАВРОВ
+1
29-01-2007 02:42

(√(8sinx+13/3))=(2cosx+2tgx) 8sinx+13/3=4cosx+8sinx+4tgx 24sinx+13=12cosx+24sinx+12sinx/cosx 12cos^4x+12sinx-13cosx=0,cosx0 12(1+cos2x)/4+12(1-cos2x)/2-13(1+cos2x)/2 6(1+cos2x)+12(1-cos2x)-13(1+cos2x)=0 6+12cos2x+6cos2x+12-12cos2x-13-13cos2x=0 cos2x=a 6a-13a+5=0 D=169-120=49 a1=(13-7)/12=1/2cos2x=1/22x=+-/3+2nx=+-/6+n,nz Проверка x=-/6 √(-4+13/3)=√(1/3)=1/√3 2*√3/2-2*1/√3=√3-2/√3=(3-2)/√3=1/√3 1/√3=1/√3 x=/6 √(4+13/3)=√(25/3)=5/√3 2*√3/2+2/√3=√3+2/√3=(3+2)/√3=5/√3 Ответ x=+-/6+n,nz

Похожие вопросы